Data and codes for "Statistical properties of quantum jumps between macroscopic states of light: reading an operational coherence record" - Mavrogordatos, Themistoklis (Stockholm University, 2026)
We propose an experimental apparatus to reveal the quantum coherence manifested in downward quantum jumps of amplitude bistability. The underlying coherent superposition of macroscopic quantum states is translated into the statistical properties of the integrated charge deposited in the detector circuit of a mode-matched heterodyne/homodyne detection scheme. At first, the dynamical evolution of a signal transmitted from an auxiliary cavity is employed to pinpoint a macroscopic switching event in a bistable main cavity subject to direct photodetection. Once the decision is made on the occurrence of a downward switch, the main cavity mode is let to freely decay to the vacuum, monitored to the production of an integrated charge. In the long-time limit, the charge distribution over an identical collection of pure states generated during the jumps converges to the Q function (heterodyne detection) or marginals of the Wigner function (homodyne detection) dictated by the phase of the local oscillator. When fluctuations over the ensemble step in, we connect the statistical properties of several switching events and the ensuing production of current records, to the cavity field correlations associated with the breakdown of photon blockade.

The present dataset contains codes and data as MATLAB .m and .mat files, respectively. Data generated and used for each figure are grouped according to the figure order in the manuscript. For example, FIG4/Qss.mat corresponds to the matrix data used to plot the steady-state Q function in inset (i) of. Fig. 4(a).

The main MATLAB code used for generating quantum trajectories in quantum amplitude bistability is titled JCRK4_Amp_Bist.m. In the script titled Direct_Adiabatic_Second.m, the coherent cancellation process is modelled. Charge trajectories and associated statistics for homodyne and heterodyne detection are generated via HetChargeHist.m and potentialHomodyne.m, respectively. The code HomCat.m accomplishes a Monte-Carlo simulation of cat-state decay trajectories under homodyne detection. Finally, the auxiliary script Qfunction.m plots Q functions of the conditioned cavity state.
Keywords: Quantum optics and quantum optomechanics; Foundations of quantum mechanics; Quantum information, computation and communication; Subatomic Physics; Subatomär fysik